2004
DOI: 10.1111/j.1547-5069.2004.04063.x
|View full text |Cite
|
Sign up to set email alerts
|

Work‐Related Disability in Canadian Nurses

Abstract: To retain and optimize scarce hospital nursing resources, strategies to address overtime, sick time, and nurse-physician relationships might provide fiscal and human benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Adequate staffing, which reduces job stress and overtime, could lead to improved efficiency along with cost effectiveness. [10]…”
Section: Discussionmentioning
confidence: 99%
“…Adequate staffing, which reduces job stress and overtime, could lead to improved efficiency along with cost effectiveness. [10]…”
Section: Discussionmentioning
confidence: 99%
“…However, using WC data to define the injury experience among these workers limited us to injury claims that were reported and accepted. Under-reporting of work-related MS injuries and disorders is widely recognized, and an understanding of injury reporting practices is needed when interpreting results of intervention effectiveness evaluations based on injury surveillance data (4,(43)(44)(45). In the hospitals we studied, underreporting of patient-handling injuries has been documented (46) and may have been influenced by the administrative change calling for reporting of an injury within 24 hours.…”
Section: Schoenfisch Et Almentioning
confidence: 99%
“…Six studies examined associations between long work hours and non- 48) of female workers and a study by O'Brien-Pallas et al 49) of nurses, both controlling for physical demands, reported long work hours were associated with increased healthcare provider visits or short-term disability claims. O'Brien-Pallas et al 49) estimated that a hospital's probability of having a high nurse lost-time claim rate increased by 70% with each 25% increase in the percentage of their nurses reporting more than 1 h of overtime per week. Allen et al 50) reported no relationship between voluntary overtime ranging up to 60+ h per week and MS injuries in workers at a truck manufacturing plant.…”
Section: Long Work Hoursmentioning
confidence: 99%